2008
DOI: 10.1897/07-600.1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and variance/covariance structure of pesticide environmental fate data

Abstract: Hydrophobicity, persistence, and volatility data for individual pesticides are widely used in risk assessment and transport modeling, so it is important to understand their distribution, variation, and covariation. Correlations (normalized covariance) among properties across a range of multiple pesticides are also important for understanding fundamental relationships among the properties. For the present study, multiple determinations of 11 physicochemical properties of 262 individual pesticides were compiled,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In addition, significant association between the two properties of KOC and SOL has been reported in several previous studies. For example, linear correlation (p<0.001) was confirmed between log-transformed KOC and SOL [24]. Similar linear relationships were also used to estimate KOC from SOL [11], [25].…”
Section: Methodsmentioning
confidence: 83%
See 4 more Smart Citations
“…In addition, significant association between the two properties of KOC and SOL has been reported in several previous studies. For example, linear correlation (p<0.001) was confirmed between log-transformed KOC and SOL [24]. Similar linear relationships were also used to estimate KOC from SOL [11], [25].…”
Section: Methodsmentioning
confidence: 83%
“…The probability distributions for AERO and KOC were derived from a database of physiochemical property and reaction half-life complied by Spurlock [24] for 172 pesticides. Spurlock [24] suggested that log normality is a reasonable assumption for AERO and KOC, and that the two properties are independent (p = 0.551).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations